Prenatal care and socioeconomic status: Effect on cesarean delivery - Carine Milcent; Saad Zbiri (Health Economics Review, 2018)
Cesarean deliveries are widely used in many high- and middle-income countries. This overuse both increases costs and lowers quality of care and is thus a major concern in the healthcare industry. The study first examines the impact of prenatal care utilization on cesarean delivery rates. It then determines whether socioeconomic status affects the use of prenatal care and thereby influences the cesarean delivery decision. Using exclusive French delivery data over the 2008-2014 period, with multilevel logit models, and controlling for relevant patient and hospital characteristics, we show that women who do not participate in prenatal education have an increased probability of a cesarean delivery compared to those who do. The study further indicates that attendance at prenatal education varies according to socioeconomic status. Low socioeconomic women are more likely to have cesarean deliveries and less likely to participate in prenatal education. This result emphasizes the importance of focusing on pregnancy health education, particularly for low-income women, as a potential way to limit unnecessary cesarean deliveries. Future studies would ideally investigate the effect of interventions promoting such as care participation on cesarean delivery rates.
Keywords: I12; I14; I18; 330; Cesarean delivery; Pregnancy care; Health education; Socioeconomic position